1979
DOI: 10.1002/cne.901860203
|View full text |Cite
|
Sign up to set email alerts
|

Spinal termination of functionally identified primary afferent neurons with slowly conducting myelinated fibers

Abstract: Single primary afferent myelinated fibers from cutaneous receptors of cat and monkey were functionally identified by recording from the spinal cord with micropipettes filled with horseradish peroxidase (HRP). Relatively slowly conducting fibers (less than 40 m/sec) from high threshold mechanoreceptors (mechanical nociceptors) and two types of low threshold mechanoreceptor (D-hair and field) were selected for staining. Iontophoresis of the HRP and subsequent histochemical reaction stained the axons recorded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
223
0
11

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(245 citation statements)
references
References 53 publications
10
223
0
11
Order By: Relevance
“…The termination pattern of BSI-B 4 binding primary sensory neurones in the spinal cord correlates closely with that of cutaneous nociceptors (Light and Perl, 1979;Sugiura et al, 1986;Kitchener et al, 1994). Furthermore, the vast majority of BSI-B 4 -labelled neurones also express the vanilloid receptor subtype 1, a molecule widely implicated in transduction of nociceptive stimuli (Guo et al, 1999;Michael and Priestly, 1999).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The termination pattern of BSI-B 4 binding primary sensory neurones in the spinal cord correlates closely with that of cutaneous nociceptors (Light and Perl, 1979;Sugiura et al, 1986;Kitchener et al, 1994). Furthermore, the vast majority of BSI-B 4 -labelled neurones also express the vanilloid receptor subtype 1, a molecule widely implicated in transduction of nociceptive stimuli (Guo et al, 1999;Michael and Priestly, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Because the pattern of BSI-B 4 binding within the rat superficial dorsal horn correlates closely with the patterns of termination of cutaneous nociceptors (Light and Perl, 1979;Sugiura et al, 1986), it has been proposed that BSI-B 4 may bind to nociceptive primary sensory neurones and consequently may be a marker for this clinically important class of neurones (Streit et al, 1986;Gerke and Plenderleith, 2001). To determine the extent to which the glycoconjugate labelled by BSI-B 4 is expressed by sensory neurones in other mammalian species, in the present study we screened the dorsal root ganglia and spinal cords of seven mammalian species for BSI-B 4 binding.…”
mentioning
confidence: 98%
“…Anatomical and physiological studies have consistently demonstrated the convergence of these inputs onto spinothalamic tract neurons in the substantia gelatinosa and deeper laminae of the spinal and medullary dorsal horn (Christensen and Perl, 1970;Chung et al, 1979;Light and Perl, 1979a;Gobel et al, 1981;Cruz et al, 1987;Rethelyi et al, 1989;Yoshimura and Jessell, 1989). Most studies have revealed a predominantly excitatory input from both fiber types with the relatively short duration postsynaptic response to stimulation of Aδ fibers preceding the C fiber response (Willis et al, 1974;Menetrey et al, 1977;Chung et al, 1979;Yoshimura and Jessell, 1989); this is consistent with the facilitatory effect of cutaneous thermal stimulation on human nocifensive reflexes (Plaghki et al, 1998).There is evidence, however, that the interactions between the central processes initiated by Aδ and C fiber stimulation are complex, as suggested by the synaptic anatomy of the substantia gelatinosa (Light and Perl, 1979b;Cruz et al, 1987;Rethelyi et al, 1989). Electrophysiological investigations reveal both inhibitory and excitatory postsynaptic responses of nociresponsive dorsal horn neurons, including inhibitory interactions mediated through the activation of Aδ and C fibers (Christensen and Perl, 1970;Chung et al, 1984a;Chung et al, 1984b;Traub and Mendell, 1988;Yoshimura and Jessell, 1989;Tsuruoka et al, 1990;Schneider and Perl, 1994;Shimizu et al, 1995;Sandkuhler et al, 1997;Liu et al, 1998).…”
mentioning
confidence: 69%
“…Neurons in the superficial dorsal horn (SDH; laminae I-II) of the spinal cord play an important role in processing noxious, thermal, and light touch stimuli before relaying this information to higher brain centers (Light and Perl 1979;Willis Jr and Coggeshall 2004). There is now increasing evidence that both noxious and innocuous stimuli are processed differently in the spinal cords of embryos, neonates, and adults.…”
Section: Introductionmentioning
confidence: 99%